Faktor Sosiodemografi terhadap Tumbuh Kembang Balita - Nova Erly Susandra; Nengyanti Nengyanti; Novrikasari Novrikasari (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the factors that influence the growth and development of toddlers. This research method is a quantitative analysis using secondary data from the 2021 Family Data Collection (PK 21). The results of this study show that statistically, the most dominant variable influencing the potential risk of stunting in children is the number of children, namely 29,812, with 95 percent CI (18,710-47,500). The variable level of the mother's education, the age of the mother who has toddlers, and the number of children in the family positively influence the growth and development of toddlers. In conclusion, the factors that affect the growth and development of toddlers are the mother's education level, age, number of children, and participating in Toddler Family Development (BKB) activities. Keywords: Toddlers, Family, Growth, and Development